ENT 530 Social Media Portfolio: Yumnolly / Tuan Aimin Syahmie Tuan Mukhtar - Tuan Mukhtar, Tuan Aimin Syahmie (2021)
This report is an attempt to comprehend how the Entrepreneurial Principles could be applied in the future. Every student in UiTM is obligated to obtain this course as part of their studies. This assignment encourages the student to carry out research on how to start and advertise a business. This even encourages an entrepreneurial mentality and decision-making process in students who desire to pursue business activities, create new businesses, or face business management obstacles. As a result, in order to create a social media business, students must exhibit innovation and communication skills. As for this report, a business named Yumnolly (SweetNibbles4U) produced fresh homemade shell and delicious filling that created by the owner itself. Yumnolly is a sole proprietorship business and has its own vision and mission. This business is located at Chendering, Kuala Terengganu. Cannoli is an Italian pastries and originally, it is contained grape wine to make the shells. However, in order to introduce cannoli to Malaysian people, we make changes to improve the recipe and wanted everyone can eat this without feeling doubted. The owner using vinegar instead of grape wine and luckily the outcome is very delicious. Furthermore, the speciality about the filling is it can create a unique combination. The combinations are like dark chocolate, vanilla and nuts. It offers the lowest price to fulfil the customer’s demand. This online business started on 6 th April 2021 and it founded by Tuan Aimin Syahmie binti Tuan Mukhtar. This report also contains the Facebook page that was created and gained over 100 likes. It also displays all of the teasers, hard sales, and soft sales that we have made and put on our Facebook page in order to attract potential customers. As everyone uses Facebook, it is the best platform for selling our products. Therefore, this report will explain how I was able to completely register with Go-ecommerce and filled out all of the information needed.